2017
DOI: 10.1016/j.ijrobp.2017.08.020
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Patients With Localized Ewing Sarcoma at Higher Risk for Local Failure: A Report From the Children's Oncology Group

Abstract: Purpose To identify clinical and treatment variables associated with a higher risk of local failure in Ewing sarcoma patients treated on recent Children's Oncology Group protocols. Methods and Materials Data for 956 patients treated with ifosfamide and etoposide–based chemotherapy on INT-0091, INT-0154, and AEWS0031 were analyzed. Local treatment modalities were defined as surgery, definitive radiation therapy (RT), or surgery plus radiation (S+RT). Five-year cumulative incidence of local failure was determi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
40
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 45 publications
(42 citation statements)
references
References 38 publications
2
40
0
Order By: Relevance
“…RT alone is an acceptable treatment for local control as well, but some evidence has suggested that surgery improved outcomes [32]. Ahmed et al showed that patients who underwent surgical resection, whether wide or less than wide, had improved survival compared to patients who did not have surgery [33]. In accordance with the prior literature, our study did not find an association between R0 surgical resection and overall survival [29, 3437].…”
Section: Discussionsupporting
confidence: 88%
“…RT alone is an acceptable treatment for local control as well, but some evidence has suggested that surgery improved outcomes [32]. Ahmed et al showed that patients who underwent surgical resection, whether wide or less than wide, had improved survival compared to patients who did not have surgery [33]. In accordance with the prior literature, our study did not find an association between R0 surgical resection and overall survival [29, 3437].…”
Section: Discussionsupporting
confidence: 88%
“…The local recurrence rate in our study is comparable to what has been found in some other studies [4, 10, 1315, 17]. However, the rate is higher than in the Children's Oncology Group study by Ahmed et al which reported a 3.6% 5 year local recurrence rate, all local recurrences occurring in the group treated by definitive RT [30]. The excellent local control observed among patients treated with excisional surgery in our study may be attributed to improvements in chemotherapy rather than to the surgical treatment of the primary tumor.…”
Section: Discussionsupporting
confidence: 87%
“…A review of outcomes for EWS in the National Cancer Database found a decreased 5-year survival in patients with radiation alone (52.5%) compared to patients treated with surgery alone (77.2%). 22 A further analysis of patients treated in a Brazilian collaborative study also found that patients treated with radiation alone for local control had considerably worse outcomes with only a 17.8% survival at 5 years when treated with radiation alone. 23 These results should be considered when evaluating the potential for complete resection of intracranial lesions and consideration for more aggressive surgery including the risks and benefits of cranioplasty.…”
Section: Discussionmentioning
confidence: 96%